Analisis Lubricant Oil Cooler pada Main Engine Di KM. Vertikal - Andriansah, Ogie; Mustholiq; Mohammad Sapta Heriyawan (Politeknik Ilmu Pelayaran Semarang, 2024)
Lubrication is one aspect that must be paid attention to, remembering that if there is a delay in lubrication or imperfect lubrication, it will result in damage to the parts that rub together. Low lubricating oil pressure is one of the factors causing imperfect lubrication in the engine. The purpose of lubrication for the performance of the main engine is to reduce friction between other components of the main engine. The aim of this research is to find out and determine the cause of the decreased performance of the Lubricant Oil cooler on the main engine at KM. Vertical, to identify the impact of decreased performance of the Lubricant Oil cooler on the main engine at KM. Vertical, To find a solution to improve the work of the main engine Lubricant Oil cooler at KM. Vertical. This research was carried out at KM. Vertical, the method used in this research is a qualitative method with the SHEL technique. The respondents were KKM and Machinists. Data collection was carried out using observation, interviews, documentation. Based on research that has been carried out, there are several factors that cause less than optimal lubrication of the oil cooler on the main engine, namely engine factors including damage to gaskets, human factors, namely the lack of understanding of the driver about the lo cooler, operational and maintenance method factors, namely incompatibility in implementing the PMS (Plan Maintenance System). ) as well as environmental factors, namely dirty sea chest filters. The impact that occurs is a decrease in the operational performance of the main engine, the performance of the lo cooler is not optimal, the temperature of the lubricating oil in the main motor increases and the pressure jacket cooling increases. Pelumasan merupakan salah satu aspek yang harus diperhatikan mengingat bahwa bila sampai terjadi suatu kelambatan dalam pelumasan atau pelumasan yang tidak sempurna makan akan mengakibatkan kerusakan pada bagian-bagian yang bergesekkan, rendahnya tekanan minyak lumas merupakan salah satu faktor penyebab tidak sempurnanya pelumasan pada mesin. Guna pelumasan bagi kinerja mesin induk yaitu untuk mengurangi gesekan antar komponen mesin induk yang lain. Tujuan penelitian ini adalah untuk Untuk mengetahui dan menentukan penyebab dari menurunnya kinerja Lubricant Oil cooler pada main engine di KM. Vertikal, Untuk mengidentifikasi dampak dari menurunnya kinerja Lubricant Oil cooler pada main engine di KM. Vertikal, Untuk menemukan solusi yang dilakukan untuk meningkatkan kerja dari Lubricant Oil cooler main engine di KM. Vertikal. Penelitian ini dilaksanakan di KM. Vertikal, metode yang digunakan dalam penelitian ini adalah metode Kualitatif dengan Teknik SHEL. Adapun responden adalah KKM dan Masinis, Pengambilan data dilakukan dengan menggunakan observasi, wawancara, dokumentasi. Berdasarkan penelitian yang telah dilakukan ada beberapa faktor yang menyebabkan kurang optimalnya lubrication oil cooler pada mesin induk yaitu faktor mesin meliputi kerusakan pada gasket, faktor manusia yaitu kurangnya pemahaman masinis tentang lo cooler, faktor metode pengoperasian dan perawatan yaitu ketidaksesuain dalam melaksanakan PMS (Plan Maintenance System) serta faktor lingkungan yaitu kotornya filter sea chest. Dampak yang terjadi adalah menurunnya kinerja operasional mesin induk, kinerja lo cooler menjadi tidak maksimal, meningkatnya suhu minyak lumas pada motor induk dan naiknya pressure jacket cooling.